The United States Marine Corps Force Design 2030 as a strategic planning process product, an appropriate framework for the Spanish military change processes? - Alegre Agulló, Carlos (Journal of the Spanish Institute for Strategic Studies, 2025)
The «age of security competition», the recent surge of war in Europe and the disruptive ways of fighting modern conflicts are pushing Western nations to update their security strategies. Spain is not immune to these influences. The study case of the Force Design 2030 of the United States Marine Corps may offer an appropriate reference frame for every force design process. The political will framed within the well-known «pivot to Asia» is guiding the Department of Defense to react against the Chinese competitivity in the Indo-Pacific region. The expeditionary oriented service of the Marines is leading one of the most acute and bold changing processes for regaining the power of the nowadays depleted deterrence. This paper analyzes this process, its alignment with the strategic objectives and its validity as comparative framework. Finally, it will be employed to extract potential lessons for the Spanish case.